Bacteriophages of Pseudomonas. (July 2010) - Ceyssens, Pieter-Jan; Lavigne, Rob
Pseudomonas species and their bacteriophages have been studied intensely since the beginning of the 20th century, due to their ubiquitous nature, and medical and ecological importance. Here, we summarize recent molecular research performed on Pseudomonas phages by reviewing findings on individual phage genera. While large phage collections are stored and characterized worldwide, the limits of their genomic diversity are becoming more and more apparent. Although this article emphasizes the biological background and molecular characteristics of these phages, special attention is given to emerging studies in coevolutionary and in therapeutic settings.